Reduction of Hydrodynamic Flow Measurement Error of Chordal Ultrasonic Flowmeter - Fedir Matiko; Vitalii Roman; Ivanna Kovalchuk (Energy Engineering and Control Systems)
In this work, ways of reducing the hydrodynamic flow measurement error of chordal ultrasonic flowmeter for the distributed location schemes of their acoustic paths are investigated. The method of calculating optimal location coordinates of the acoustic paths of ultrasonic flowmeters is considered in detail, using the analytical-empirical power law of the distribution of the velocity of the undistorted flow. As a result of the work, the authors calculated the optimal arrangement of acoustic paths for chordal schemes of two- and three-path ultrasonic flowmeters. It was established that optimization of the location scheme of the acoustic paths of chordal ultrasonic flowmeters allows reducing the hydrodynamic flow measurement error to the value of 0.05 % (for two-path flowmeters) and 0.1 % (for three-path). The developed approach is convenient when designing multipath ultrasonic flowmeters and their research in laboratory conditions.